Sighting of the rare Poey’s scabbardfish, Evoxymetopon poeyi, in the Polynesian triangle - Fabres, Alejandra A. (Revista de Biología Marina y Oceanografía, 2020)
Rapa Nui only allows artisanal fishery activities, but these often go unaware. The market is centralized on Pacific chub, snoek and yellowfin tuna, all common pelagic fish. On September 2016, one un-identified specimen was caught off-shore as by-catch, and left on the main port at Hanga Piko. The objective of this study was to identify the specimen to a species level, using a morphological, meristic and molecular approach. All analyses suggest that the specimen belongs to a Poey’s scabbardfish, Evoxymetopon poeyi. Concluding that the rare Poey’s scabbardfish, has an oceanic distribution through seamounts as a mid-water migrator.